Novel DNA Barcode Sequences to Authenticate the Seven Outstanding Canarium Ovatum, (PILI) Varieties from the Pili Research and Technology Development Center, Tabaco City, Albay - Camposano, Imelda Corazon (Archīum Ateneo, 2021)
This is the first report on the novel DNA barcode sequences, matK and ITS genes, to authenticate the seven outstanding Canarium ovatum varieties – namely, Lanuza, Laysa, Magayon, Magnaye, Mayon I, M. Orolfo, and Orbase. These varieties are registered under the National Seed Industry Council (NSIC) and cultivated at the Pili Research and Technology Development Center (PRTDC), in Brgy. Buang, Tabaco City, Albay. C. ovatum is an important economic crop in the Bicol region and is sold for commercial purposes. In this study, genomic DNA extraction was done using the cetyltrimethylammonium bromide (CTAB) method. Extracted DNA was amplified, rbcL exhibited 100% amplification success while both matK and ITS demonstrated 89.45% amplification success. For rbcL, amplicon sizes based on agarose gel electrophoresis across (AGE) all accessions were ~700 bp while their sequence length ranged from 711 bp to 739 bp with an average of 722 bp. Meanwhile, amplicon sizes of matK genes across all accessions were ~900 bp while their sequence length ranged from 786 bp to 911 bp with an average of 881 bp. For ITS genes, amplicon sizes based on AGE across all accessions were ~400 bp while their sequence length ranged from 321 bp to 485 bp with an average of 432 bp. Maximum Likelihood phylogenetic trees were constructed using the Tamura-Nei model with bootstrap support of 1000 replications to determine the confidence estimate of the trees. Rooted phylogenetic tree based on rbcL sequences shows that the seven varieties of C. ovatum including the standard variety ‘Katutubo’, Camalig I, Camalig II, and Tabaco 5 were grouped into the same clade with bootstrap support values ranging from 86% to 99%. Based on rbcL sequences, the seven varieties including the standard variety ‘Katutubo’ may have v originated from the legacy trees, Camalig I, Camalig II, and Tabaco 5. On the other hand, rooted phylogenetic trees based on matK sequences show that the seven varieties of C. ovatum including the standard variety ‘Katutubo’, Camalig II, and Tabaco 4 were grouped into the same clade with bootstrap support values ranging from 63% to 96%. This shows that the seven varieties including the standard variety ‘Katutubo’ may have originated from the legacy trees, Camalig II and Tabaco 4. For phylogenetic analysis using ITS sequences, the seven varieties were divided into four groups. The rooted phylogenetic tree shows that Lanuza var., M. Orolfo var., Magnaye var., and Mayon var., were grouped into the same clade with bootstrap support values ranging from 57% to 100%. These varieties possibly originated from the legacy trees, Tabaco 5, Camalig I, and Camalig II. Magayon var. and Laysa var. may have originated from the legacy trees, Tabaco 1, 2, and 4 as they were grouped into the same clade with bootstrap support values ranging from 80% to 86% while Orbase var. and Sorsogon 2 formed two separate clades with a bootstrap support value of 59%. Based on ITS sequences, these four groups possibly originated from the legacy trees, Sorsogon 1 and 3. Results showed that at less than 1% sequence divergence, rbcL discriminated 90% of species pair, matK discriminated 78%, and ITS discriminated 67% of species pair. Between 1% to 5% sequence divergence, matK discriminated 1% of species-pair, rbcL discriminated 10%, and ITS discriminated 22%. At more than 5% sequence divergence, rbcL discriminated 0%, matK discriminated 21%, and ITS discriminated 11% of species-pair. The average evolutionary divergence over all sequence pairs is 0.2% for rbcL, 12% for matK, and 6% for ITS. The results of this study suggest that matK and ITS are more efficient than rbcL in discriminating samples of the same species. The DNA marker, rbcL, underperformed matK, and ITS as a DNA barcode. For C. ovatum species, matK and ITS proved to be the most effective DNA markers. This vi study serves as baseline data for the identification of C. ovatum varieties. For the Pili industry, this study on DNA barcoding is beneficial to promote awareness of this underutilized plant species having valuable nutritional properties not just on a local level but on a global scale. DNA barcoding of C. ovatum varieties is relevant, especially for food safety and security, in food traceability, food quality control, legal logging, trade, and even in investigations of poison derived from plants.